Increased pre-transplant carotid intima-media thickness is associated with early post-transplant atrial fibrillation, stroke, and reduced survival after heart transplantation - Heil, Karsten M.; Rivinius, Rasmus; Helmschrott, Matthias; Rahm, Ann-Kathrin; Ehlermann, Philipp; Frey, Norbert; Darche, Fabrice Fernand (Life, 2025)
Background: Carotid intima-media thickness (CIMT) is an established risk factor for adverse cardiovascular events in the general population, but its impact on patients after heart transplantation (HTX) remains unknown. We investigated the effects of an increased pre-transplant CIMT > 0.9 mm on outcomes after HTX. Methods: This observational retrospective single-center study included 311 patients receiving HTX at Heidelberg Heart Center between 2002 and 2014. Patients were stratified by degree of pre-transplant CIMT (CIMT ≤ or >0.9 mm, threshold defined by ESC guidelines). Analysis covered donor and recipient demographics, post-transplant medications, mortality (including causes of death after HTX), early post-transplant atrial fibrillation (AF), and stroke after HTX. Results: A total of 37 of 311 HTX recipients (11.9%) had a pre-transplant CIMT > 0.9 mm. These patients showed an increased 10-year post-transplant mortality (81.1% versus 41.2%, p < 0.001) and had a higher percentage of death due to graft failure (24.3% versus 10.6%, p = 0.017), as well as due to thromboembolic events/bleeding (10.8% versus 2.9%, p = 0.019). Multivariate analysis demonstrated pre-transplant CIMT > 0.9 mm as an independent risk factor for 10-year mortality after HTX (HR: 2.599, 95% CI: 1.683-4.014, p < 0.001). Secondary outcomes showed a significantly higher rate of 30-day post-transplant AF (27.0% versus 10.9%, p = 0.006) and 30-day stroke after HTX (10.8% versus 1.1%, p < 0.001) in patients with a pre-transplant CIMT > 0.9 mm. Conclusion: Pre-transplant CIMT > 0.9 mm is a prognostic marker for early post-transplant AF, stroke, and reduced long-term survival after HTX. Preventive measures, including close monitoring and management of cardiovascular risk factors, are warranted in these high-risk patients.
Veröffentlicht: 1. Oktober 2025
Gesehen am 01.12.2025